Celebrity endorser and respondents gender: Its impact on company, behavioral and attitudinal variables - Phang, Grace; de Run, Ernest Cyril (Jurnal Kemanusiaan, 2007)
The use of and literature on celebrity endorsers is extensive. Nevertheless there is limited study on the impact of such use to a company’s image by respondent’s gender and replication of past findings in a Malaysian context. This study utilizes a factorial design to measure the interaction of the use of celebrity endorser and target market reaction by gender and its impact on the company, behavioral and attitudinal variables. The findings show no significant difference for all variables between advertisements that have a celebrity endorser and those that don’t, except for attitude towards the company for female respondents. There were weak overall interaction effects for the variables attitude towards the company and word of mouth. Behavioral responses were consistently lowest. Highest was attitudinal variables followed by attitude towards the company.